Perancangan Sistem Pendukung Keputusan Web AHP Penerima Rumah Gratis Bappelitbang Sumatera Utara - Siregar, Ridho Albar; Sipayung, Muhammad Irfan Afandi; Sinaga, Imam Adlin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The fairness and accuracy of social aid distribution, such as the free housing program initiated by Bappelitbang North Sumatra, are constantly challenged by issues of subjectivity and misidentification of targets. Manual selection processes are often susceptible to internal biases and human intervention, leading to aid not reaching the most deserving families. This study addresses this critical gap by designing a Web-Based Decision Support System (DSS) utilizing the Analytic Hierarchy Process (AHP) method. The AHP algorithm is employed to structure the complex selection problem into hierarchical criteria and sub-criteria, enabling objective prioritization through pairwise comparison. The system’s architecture is designed to capture, process, and weigh crucial factors affecting family eligibility (e.g., income, dependency status, building condition) to derive a definitive qualification score. The development incorporates PHP, MySQL, and JavaScript to create an accessible and transparent platform. The primary objective of this system is to eliminate subjectivity and ensure optimal target accuracy in the qualification process. By generating a weighted ranking of applicants based purely on predefined criteria, the system provides Bappelitbang with an accountable and transparent tool. This shift from manual assessment to a computational model significantly enhances the integrity of the selection, guaranteeing that the free housing assistance is allocated to the most qualified members of the community.